Understanding bacterial communities for informed biosecurity and improved larval survival in Pacific oysters - Laroche, O; Symonds, JE; Smith, KF; Banks, JC; Mae, H; John Bowman; Pochon, X (2018)
Bacteria are ubiquitous in all marine habitats and can be beneficial or detrimental to the survival and growth of shellfish raised in aquaculture. To reduce the exposure of cultured shellfish to potential pathogens, antibiotics can be used. However, risks associated with this practice have led to the development of alternative techniques such as ultraviolet (UV) light exposure for seawater disinfection. In this study, we used 16S rRNA gene metabarcoding to measure the effect of low (50 mJoules/cm 2 ) and high (200 mJoules/cm 2 ) UV treatment of seawater on the bacterial communities present in hatchery rearing water and in Pacific oyster Crassostrea gigas larvae. 81 samples were collected between 13 and 29 March 2017 for high-throughput DNA sequencing of bacterial communities, including differentially-treated seawater, the microalgae fed to the oysters and oyster larvae (fertilized eggs, early veliger larval stage [D-larvae], and pre-settlement stage) samples. Differences in larval mortality between low and high UV treatments were also assessed. We found that the two UV treatments influenced the overall bacterial community diversity and affected its composition in both seawater and oyster larval samples. While alpha-diversity was mostly driven by the UV treatment, we found that the microbiome composition was primarily affected by temporal changes in the water source. Compared to the bacterial microbiome associated with seawater, the oyster larvae microbiome changed more significantly in response to both UV treatments and sampling dates with marked shifts in the dominant bacteria associated with fertilized eggs (class Gammaproteobacteria , families Rhodospirillaceae and Pelagibacteraceae ), the D-larvae (family Alteromonadaceae ), and the pre-settlement larvae (families Flavobacteriaceae and Rhodobacteraceae ). As larval development progressed, an increasingly complex bacterial community structure was observed. These bacterial community changes were likely driven by multiple factors, including the microbiome ...